THE SHARIA COMPLIANCE ANALYSIS OF MUSYARAKAH FINANCING IN ISLAMIC RURAL BANK OF AMANAH SEJAHTERA GRESIK - Ita Miftahul Janah; Sunan Fanani (Universitas Airlangga, 2020)
The background of this research is the growth and development of the Islamic economy in Indonesia these days. It can be seen from the number of Islamic Financial Institutions that have emerged lately and offered products that are free of usury. Thus, citizens’ perceptions of Islamic banks and conventional banks are the same. Meanwhile, to carry out its operations, sharia financial institutions must follow Islamic law (Sharia law), which are regulated in the DSN-MUI Fatwa and supervised by the Sharia Supervisory Board. From the phenomenon above, the writer wants to raise the theme of sharia compliance in sharia financial institutions namely musyarakah financing in Islamic Rural Banks. This study uses qualitative descriptive analysis, a case study approach. The object of this research is the Islamic rural bank (BPRS) Amanah Sejahtera Gresik. To examine the compliance of the musyarakah contract, the author uses the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI Fatwa) No.08/DSN-MUI/IV/2000 as its reference. The results show that the BPRS Amanah Sejahtera Gresik has been operating the Musyarakah Financing following the applicable DSN-MUI Fatwa rules. In addition to that, besides seeking profits, BPRS also preaches Islamic economics. From the sharia principles that have been carried out by the BPRS, the purpose of maqashid sharia is fulfilled.Keywords: Sharia Compliance, Musyarakah, BPRS Amanah Sejahtera, DSN-MUI Fatwa, Maqashid Sharia.REFFERENCEAfandi, Ahmad Hafid. (2017). Implementasi mitigasi sharia non-compliance risk pengembangan produk keuangan syariah Di Bank Pembiayaan Rakyat Syariah (BPRS) (Studi Kasus: PT BPRS Mandiri Mitra Sukses. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Ainiyah, Ainin. (2017). Kepatuhan Syariah (Shariah Compliance) Akad Mudharabah di Baitul Maal Wa Tamwil Bina Insan Mandiri (BMT-BIM) Cabang Rengel-Tuban. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Al-Quran dan Terjemahnya. (2016). Jakarta: Kementerian Agama Republik Indonesia.Antonio, M. S. (2001). Bank syariah dari teori ke praktik. Jakarta: Gema Insani Press dengan Tazkia Cendekia.Apita, Gendrabagus. (2012). Analisis ketaatan syariah (sharia compliance) akad murabahah di BMT UGT Sidogiri. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Ascarya. (2012). Akad dan produk bank syariah. Depok: Rajagrafindo Persada.Ash Shiddieqy, Teungku Muhammad Hasbi. (1997). Pengantar ilmu fiqh. Semarang: PT Pustaka Rizki Putra.Departemen Perbankan Syariah Ototritas Jasa Keuangan (DPBS-OJK). (2016). Standar produk perbankan syariah musyarakah dan musyarakah mutanaqishah. Jakarta.Fadla, Melati. (2017). Analisis kepatuhan syariah pada BNI Syariah, Bank Syariah Mandiri, dan Bank Muamalat Indonesia. Skripsi tidak diterbitkan. Bogor: Institut Pertanian Bogor.Fanni, Alfina Taswirul. (2016). Kepatuhan syariah akad mudharabah dalam produk pembiayaan kepada koperasi untuk anggota. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Firdaus, Jasri. (2013). Bank Perkreditan Rakyat Syariah-BPRS.Hidayah, Arini. (2017). Perbedaan sistem bagi hasil pada pembiayaan al mudharabah dan al musyarakah di PT. Bank Jatim Unit Usaha Syariah Kantor Pusat Surabaya. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Huda, N. (2010). Lembaga keuangan Islam:Tinjauan Teoritis dan Praktik. Jakarta: Prenada Kencana Media Group.Irwan, Rezafitria dan Dewi. (2013). Analisis prosedur pembiayaan mudharabah berdasarkan fatwa DSN-MUI No.07/DSN-MUI/IV/2000 dan PSAK 105: Studi Kasus Pada Bank Syariah XYZ. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Islami, Muhammad Danial. (2017). Pembiayaan musyarakah oleh bank syariah pada bisnis waralaba agen wisata perjalanan. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Mardani. (2012). Fiqh ekonomi syariah: fiqh muamalah. Jakarta: Kencana.Mardiyan, Sepki. (2015). Tingkat Kepatuhan Syariah Di Lembaga Keuangan Syariah, Jurnal Akuntansi dan Keuangan Islam, 3(1), 57-68.MUI. (2013). Fatwa DSN-MUI Nomor 08/DSN-MUI/IV/2000. Tentang Pembiayaan Musyarakah.Muhammad, (2009). Model-model akad pembiayaan di bank syariah. Yogyakarta: UII Pres.Naf’an. (2014). Pembiayaan musyarakah dan mudharabah. Yogyakarta: Graha Ilmu.Raharjo, M. D. (1999). Islam dan tantangan transformasi sosial ekonomi. Jakarta: Lembaga Agama dan Studi Filsafah.Salman, Kautsar Riza. (2018). Pengaruh kinerja maqashid syariah, tingkat tata kelola Islami, dan karakteristik perusahaan terhadap tingkat agresivitas pajak dan tingkat pelaporan sosial Islam pada bank umum syariah di Indonesia. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Sudarsono, H. (2012). Bank dan lembaga keuangan syariah. Yogyakarta: Ekonisia.Syauqoti, Rolfatus dan Mohammad Ghozali. (2018). Analisis sistem lembaga keuangan syariah dan lembaga keuangan konvensional. Ponorogo: Universitas Darussalam Gontor.Yin. Robert K. (2003). Studi kasus: desain dan metode, Terjemahan. Jakarta: Raja Grafindo Persada.Zaenah. (2018). Prinsip hukum akad musyarakah mutanaqishah perbankan syariah. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.